1993
DOI: 10.3354/meps096259
|View full text |Cite
|
Sign up to set email alerts
|

Community metabolism and air-sea C02 fluxes in a coral reef ecosystem (Moorea, French Polynesia)

Abstract: Community metabolism (primary production, respiration and calcification) and air-sea CO2 fluxes of the 'Tiahura barrier reef' (Moorea, French Polynesia) were investigated in November and December 1991 Gross production and respiration were respectively 640.2 to 753 and 590.4 to 641.5 mm01 (02 or CO2) m-' d-l (7.7 to 9.0 and 7.1 to 7.7 g C m-2 d ') and the reef displayed a slightly negative excess (= net) production. The contribution of planktonic primary production to reef metabolism was negligible (0.15 ?4, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 10 publications
9
129
2
4
Order By: Relevance
“…The dissolution of CaCO 3 leads to the decrease in the surrounding waters of CO 2 transferred to the HCO 3 { pool. These processes combined with NCP to control the release or uptake of CO 2 by a given ecosystem to or from the surrounding water, and determine to a large extent the status of the ecosystem as a source or sink of atmospheric CO 2 (e.g., Gattuso et al 1993Gattuso et al , 1998Frankignoulle et al 1994;Borges 2005). The net CaCO 3 production in P. oceanica meadows induces a release of CO 2 of about 46% of CO 2 fixed by NCP to the surrounding waters based on the DIC approach (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The dissolution of CaCO 3 leads to the decrease in the surrounding waters of CO 2 transferred to the HCO 3 { pool. These processes combined with NCP to control the release or uptake of CO 2 by a given ecosystem to or from the surrounding water, and determine to a large extent the status of the ecosystem as a source or sink of atmospheric CO 2 (e.g., Gattuso et al 1993Gattuso et al , 1998Frankignoulle et al 1994;Borges 2005). The net CaCO 3 production in P. oceanica meadows induces a release of CO 2 of about 46% of CO 2 fixed by NCP to the surrounding waters based on the DIC approach (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Air-sea CO 2 flux values may be used to differentiate coral reefs that act as either sinks or sources of atmospheric CO 2 [6][7][8][9][10][11][12][13][14][15][16][17][18]. Positive values typically characterize coral reefs as a source of atmospheric CO 2 , whilst negative values may [20].…”
Section: Coral Reefs Of the Scs Act As Sources Of Atmospheric Comentioning
confidence: 99%
“…In recent years, several studies have examined the role of coral reefs and their contribution to atmospheric CO 2 by measuring seawater pCO 2 and atmospheric pCO 2 in coral reefs [6][7][8][9][10][11]. They indicate that although coral reefs are mostly net sources [7][8][9][10][11][12][13][14][15][16] of atmospheric CO 2 , they may also act as sinks [6,17,18] for atmospheric CO 2 . Suzuki et al [6] suggested that the contribution of coral reefs to atmospheric CO 2 is largely dependent on their topographic and oceanographic settings.…”
mentioning
confidence: 99%
“…In addition to physical and environmental forcings, organic and inorganic metabolic processes significantly alter the chemical properties of the water. Photosynthesis and respiration and calcification and dissolution are opposing forces for changes in pCO 2 (Smith and Key 1975) and other components of the carbonate system (Morse and Mackenzie 1990;Gattuso et al 1993Gattuso et al , 1996Yates and Halley 2006). Thus, determination of the physical and biological forcings driving changes is often difficult.…”
Section: Coral Reef Metabolism In Coastal Environmentsmentioning
confidence: 99%